2023
DOI: 10.1021/jacs.2c10650
|View full text |Cite
|
Sign up to set email alerts
|

Graphite-like Charge Storage Mechanism in a 2D π–d Conjugated Metal–Organic Framework Revealed by Stepwise Magnetic Monitoring

Abstract: Quasi-two-dimensional (2D) fully π–d conjugated metal–organic frameworks (MOFs) have been widely employed as active materials of secondary batteries; however, the origin of their high charge storage capacity is still unknown. Some reports have proposed a mechanism by assuming the formation of multiple radicals on one organic ligand, although there is no firm evidence for such a mechanism, which would run counter to the resonance theory. In this work, we utilized various magnetometric techniques to monitor the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…The stacking of two-dimensional (2-D) semiconductive nanosheets, such as graphene, MoS 2 , and h-BN, provides an unprecedented chance to produce functional Moiré materials with the exceptional electronic properties, optronic properties, and catalytic activities. New 2-D porous materials, for example, 2-D metal–organic frameworks (2-D MOFs) and 2-D covalent-organic frameworks (2-D COFs) also arouse remarkable attention due to their highly exposed active sites and designable pore environment that affords high-performance adsorption, separation, sensing, and catalysis. Their pore characteristics conventionally depend on the intrinsic pore sizes and shapes from intralayer constitutions .…”
Section: Introductionmentioning
confidence: 99%
“…The stacking of two-dimensional (2-D) semiconductive nanosheets, such as graphene, MoS 2 , and h-BN, provides an unprecedented chance to produce functional Moiré materials with the exceptional electronic properties, optronic properties, and catalytic activities. New 2-D porous materials, for example, 2-D metal–organic frameworks (2-D MOFs) and 2-D covalent-organic frameworks (2-D COFs) also arouse remarkable attention due to their highly exposed active sites and designable pore environment that affords high-performance adsorption, separation, sensing, and catalysis. Their pore characteristics conventionally depend on the intrinsic pore sizes and shapes from intralayer constitutions .…”
Section: Introductionmentioning
confidence: 99%
“…The Cu 2p spectrum is still dominated by Cu + further discharged to 1.0 V, which is similar to the redox reaction of Cu 2+ /Cu + in other conjugated coordination compounds. 31,37 Aer being fully charged to 3.0 V, the Cu-TABQ can be returned to the initial state. Besides, the C 1s spectra are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…). 21,33–37 Therefore, it is desirable to combine TABQ and Cu 2+ into a MOP skeleton to achieve high energy-density organic cathodes for SIBs and explore the Na + /e − transfer mechanism and structural evolution during the charge/discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…The EPR spectra of Cu 3 (HHTP) 2 exhibited a broad isotropic signal which is a characteristic of the Cu­(II) ions arranged in the square planar coordination environment, along with the presence of a weak signal corresponding to the HHTP radicals (Figure c). Furthermore, the radical concentration in Cu 3 (HHTP) 2 was estimated from the EPR spectra, and it was observed that only ∼0.03% of spins originated from the ligand radicals (can be assigned as defect states) (Figure S15). Nonetheless, in such systems, the estimation of radical concentration cannot be precise, as the radicals in Cu 3 (HHTP) 2 are not static due to the redox activity of the HHTP in M-HHTP systems (multielectron redox process within −0.009 to −0.865 V) as well as the small redox potential for Cu­(II)/Cu­(I) couple [E 0 (Cu 2+ /Cu + ) = 0.153 V] which leads to continuous charge delocalization between the Cu d orbitals and the π orbitals from HHTP.…”
Section: Resultsmentioning
confidence: 99%
“…In this direction, Awaga and co-workers recently investigated a π−d conjugated 2D MOF Cu-THQ (THQ = tetrahydroxy-1,4-benzoquinone), where they observed voltage-induced charge delocalization between the metal d-orbitals and ligand π-orbitals. 36 The spin interaction was studied in-depth using cyclic voltammetry and EPR spectroscopy. Taking inspiration from their work, here, we have introduced an innovative design strategy of selectively introducing diamagnetic S = 0 Zn(II) ions in place of paramagnetic S = 1/2 Cu(II) ions, to experimentally observe the intertwining of the localized (d-electrons) and delocalized (π-electrons) S = 1/2 spins toward the emergence of the possible spin frustrated state in M 3 (HHTP) 2 -based materials (Figures S2 and S3).…”
Section: ■ Introductionmentioning
confidence: 99%